Integration of Indigenous Knowledge in School Education and NEP-2020 - Sagarika, B. (International Journal of Psychosocial Rehabilitation, 2020)
Indigenous knowledge and traditional ways of learning will be covered and included in mathematics, astronomy, philosophy, yoga, architecture, medicine, agriculture, engineering, linguistics, literature, sports, and games, as well as in governance, polity, and conservation." Students in secondary school will also have the option to take an interesting course on Indian Knowledge Systems. The inclusion of Indigenous traditional knowledge (ITK) in the NEP 2020 vision is a crucial component. Indigenous Traditional Knowledge (ITK) is an essential component of a community's culture and history. It has developed over many years of consistent experimenting with daily living and the resources that are close to the community. It is the distinct, age-old local knowledge that has grown up around and within the particular circumstances of men and women who are native to a given region. Indigenous traditional knowledge systems aid us in realising that there are various lenses through which we might perceive and learn about the world. To maintain the survival, transfer, and maintenance of knowledge and worldviews that support spirituality, abundance, balance, resilience, adaptability, sustainability, living within the carrying capacity, and making decisions collectively for the good of everyone, indigenous education is necessary. It will accelerate growth, particularly in our nation, which has a thriving and wonderful culture.